Developing quality and performance of construction using 3D model in building information modelling - Nurul Intan Shafiqa, Shahiri (2018)
The purpose of this study is to explore the potential of BIM (Building Information Modeling) technology used for the management and maintenance of more specialized building construction procedures. It focuses on the concept of objects and is dedicated to the 3D (three-dimensional) description of the built environment. It allows its description and representation holistically, by describing objects constructed over more or less detail scale, and complex, if one combines a set of geometric and non-geometric data with the possibility of parametrization of the object. Additionally, this study investigates the BIM 3D model trading alignment process for challenges and problems through a case study approach and offers insights for continuous improvement.